Singularity of grade school pupils anxiety - VINARCHIK, Elena (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2014)
Features of the correction program sent to the decline of level of anxiety ofGrade school pupils by the methods of musical therapy.